Shadowed ground : America's landscapes of violence and tragedy - Foote, Kenneth E., 1955- (University of Texas Press, 2003)
Shadowed Ground explores how and why Americans have memorialized - or not - the sites of tragic and violent events spanning three centuries of history and every region of the country. For this revised edition, Kenneth Foote has written a new concluding chapter that looks at the evolving responses to recent acts of violence and terror, including the destruction of the Branch Davidian compound at Waco, Texas, the Oklahoma City bombing, the Columbine High School massacre, and the terrorist attacks of 9/11.